2021
DOI: 10.1108/xjm-09-2020-0118
|View full text |Cite
|
Sign up to set email alerts
|

Financial inclusion in north-eastern region: an investigation in the state of Assam

Abstract: Purpose Access to finance, especially by the poor and marginalized section of the population, is a prerequisite for creating employment opportunities, economic growth, poverty reduction and social cohesion. Access to finance makes transactions quicker, cheaper and safer. Most people around the world having an account in a formal financial institution serve as an entry point into formal financial sector. This study aims to analyze the status of financial inclusion in Assam with respect to demographic penetratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Jungo et al (2022) result indicated that there is no statistically significant effect of financial regulation on financial stability in SSA countries. Maity and Sahu's (2021) result indicated that a significant difference between Assam and aggregate Indian financial inclusion and the status of Assam is somewhat lower as compared to the aggregate financial inclusion status of India. Johnpaul and Patience's (2021) result showed that SMEs in Nigeria have access to financial products that are made available by banks and other financial institutions.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Jungo et al (2022) result indicated that there is no statistically significant effect of financial regulation on financial stability in SSA countries. Maity and Sahu's (2021) result indicated that a significant difference between Assam and aggregate Indian financial inclusion and the status of Assam is somewhat lower as compared to the aggregate financial inclusion status of India. Johnpaul and Patience's (2021) result showed that SMEs in Nigeria have access to financial products that are made available by banks and other financial institutions.…”
Section: Introductionmentioning
confidence: 91%
“…Moreover, competitiveness negatively impacts financial stability, and financial regulation moderates the negative effect of competitiveness on financial stability in SSA and LAC countries. Regarding the practical implications, this study shows that fostering financial inclusion in the countries under study contributes significantly to improving the welfare of households and especially to the stability of the financial system Maity and Sahu (2021). examined financial inclusion in the north-eastern region: 126 Article DOI: 10.52589/AJAFR-RGJVRPCF DOI URL: https://doi.org/10.52589/AJAFR-RGJVRPCF www.abjournals.org financial regulatory oversight, thereby increasing financial inclusion and contributing to poverty reduction and income disparity reduction.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Maity and Sahu (2018b) also found existence of financial inclusion disparity between the regions and states in India. Further, Maity (2019), Maity and Sahu (2021) and Ghosh and Sahu (2021) have also found existence of disparity in financial inclusion. Sharma (2016) in her study suggested positive nexus between geographic/demographic outreach of ATMs/branches and growth of Indian economy.…”
Section: Review Of Literaturementioning
confidence: 97%
“…They have calculated FI index for both formal and informal sources of the demand side. In another study, Maity and Sahu (2021a) have measured the FI status of Assam, a north-eastern region state, and compared it with overall India.…”
Section: Review Of Literaturementioning
confidence: 99%